Adult Eyewitness Memory for Single Versus Repeated Traumatic Events. Issue 2 (28th March 2017) - Theunissen, Tjeu P.M.; Meyer, Thomas; Memon, Amina; Weinsheimer, Camille C.
Summary: Reports from individuals who have witnessed multiple, similar emotional events may differ from reports from witnesses of only a single event. To test this, we had participants (N = 65) view a video of a road traffic accident. Half of the participants saw two additional (similar) aversive films. Afterwards, participants filled out the Self‐Administered Interview on the target film twice with an interval of 1 week. Participants who saw multiple similar films were less accurate in recalling details from the target film than participants in the control condition. On their second report, participants were less complete but more accurate compared with their first report. These results indicate that adults who have witnessed multiple repeated events may appear less reliable in their reports than adults who have witnessed a single event. These findings are relevant when evaluating eyewitness evidence and call for new approaches to questioning witnesses about repeated events.Copyright © 2017 John Wiley & Sons, Ltd.